This and That in the Language of Film Dubbing: A Corpus-Based Analysis - Pavesi, Maria (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
Recent research in audiovisual translation has focussed on the language of both original and translated dialogue, revealing different degrees of alignment between fictional dialogue and spontaneous conversation. In this context, demonstratives deserve special attention as they are major means to highlight segments of the current discourse and extra-linguistic reality in speech and may play a significant role in cinematic language as well. Furthermore, demonstratives are an area of dissimilarity between languages, with their translation being potentially subject to interference from the source to the target text. Through a quantitative corpus-based approach, this study explores to what extent demonstratives occur in the language of Italian dubbing, how similar in this respect dubbed dialogue is to Italian spoken language and what translation operations may account for the observed translation outcomes. Drawing on a small English-Italian parallel corpus of film dialogue, all English demonstrative pronouns have been coded for syntactic role, pragmatic function and translation operation. Results show that demonstratives occur to a lesser extent in dubbed film language vis-à-vis both Italian conversation and the source English dialogues. These findings are discussed in terms of the cross-linguistic contrast between Italian and English as well as the convergence of dubbed dialogue towards the model of original Italian film language.